Faktor-Faktor Penentu Minat Beli Remaja Masjid Terhadap Produk Korea: Studi Empiris Pada Mie Samyang dengan Memperhatikan Label Halal, Harga, Dan Citra Merek - Aresta, Fadzillah; Rohimat, Asep Maulana (Journal of Economics and Business Research (JUEBIR), 2023)
This research aims to identify the determinants of purchase intent among mosque youth for Korean products, specifically focusing on Samyang Instant Noodles, considering the factors of Halal Label, Price, and Brand Image. The research sample comprises 150 respondents of mosque youth in Boyolali, selected using non-probability sampling. Mosque youth are considered a group that integrates religious aspects with contemporary trends and digital literacy. The research employs a quantitative method with a questionnaire as the data collection instrument. The collected data are analyzed using the statistical SPSS version 22. The findings reveal that the Halal Label has a positive and significant impact on the purchase intent of mosque youth. Conversely, Price negatively influences purchase intent, while Brand Image does not have a positive or significant effect on purchase intent. Simultaneously, the Halal Label, Price, and Brand Image collectively exert a positive and significant influence on the purchase intent of mosque youth towards Samyang Instant Noodles. These results offer insights for industry stakeholders to understand the preferences and factors influencing the purchase intent of mosque youth for Korean food products.